The frontal weapon of the termite Armitermes euamignathus Silvestri (Isoptera, Termitidae, Nasutitermitinae) - Costa-Leonardo, Ana Maria [UNESP] (Sociedade Brasileira de Zoologia, 2001)
Frontal weapon is the term used to designate the apparatus consisting of frontal gland and associated structures that participate in the chemical defense of termite soldiers. The ultra structure of the frontal gland and the scanning microscopy of the soldier head was investigated in the termite Amiitermes euamignathus Silvestri, 1901.Campaniform sensilla was not observed but there were 80 to100 sensory bristles around the frontal pore. The glandular epithelium shows only class 1 cells according 10 the classification of NOIROT & QUENNEDEY (1974, 1991). The glandular cells are characterized by apical microvilli, a basal labyrinth and a large quantity of smooth endoplasmic reticulum which forms dense zones throughout the cytoplasm. The secretion is concentrated mainly in the basal pole of the cell and consists of large lipid droplets. The secretory epithelium is covered by a thick apical cuticle composed of a thin outer epicuticle, a layer of epicuticular filaments and a dense procuticle. The cytological results concerning the frontal pore showed a reduced cuticle and the presence of a subcuticular space where the lipid droplets are accumulated. The lack of class 3 cells and the presence of an intrinsic musculature are two anatomical features of the A. euamignathus frontal gland that will be important in the phylogenetic relationships of the Nasutitermitinae.
Keywords: Isoptera; Armitermes euamignathus; frontal weapon; frontal gland; exocrine glands